A Study to Adapt Raw Clay Housing to Climate Change: The Locust Bean Tree (Parkia biglobosa) was Used as Protective Material - Samah Ouro-Djobo Essoavana; Amey Kossi Bollanigni; Sanya Emile; Vianou Antoine; Atcholi Esso Kokou (Advanced Aspects of Engineering Research Vol. 16, 2021)
Raw clay has been used in housing construction from ancient times and is still used now. Traditional habitat, which consists of diverse buildings scattered around our earth, provides proof. Rain water wash, among any other pathologies impacting naked earthen walls, is a serious concern that requires careful consideration. This explains why this study on the protection mechanisms for these types of walls is so interesting. This article describes an experiment with low walls built of raw clay mixed with composite protective materials (both traditional and modern), which were subjected to intense flooding. The locust bean tree (local tree) fruit husk extract applied to raw clay mortar and correctly blended appears to provide superior ability to protect walls from water assault, according to the results of the tests examined through the efficiency of the protecting materials. In addition, consistency and plasticity tests showed improved performance in clay material qualities. Research carried out shows that the decoction of pods of Parkia biglobosa (néré) is rich in tannins compounds including gallic acid, epicatechin gallate and epigallocatechin.